POLICY PROVISIONS ON LANGUAGE OF INSTRUCTION AND CURRICULUM IMPLEMENTATION BY LANGUAGE TEACHERS IN BASIC EDUCATION SCHOOLS IN NIGERIA - MUSA, MUSA JAURO; BAKURA, FATIMA USMAN (Sokoto Educational Review, 2025)
This paper examines the policy provisions on the language of instruction and curriculum implementation by language teachers in basic education schools in Nigeria, as stipulated in the National Policy on Education (NPE, 2014): three languages for Basic 1-3, four languages for Basic 4-6, and in upper basic education schools. The objective of this paper is to outline the languages stipulated in the curriculum for the comprehension of language teachers in basic education schools and to clearly state the language of the curriculum used as a medium of instruction, as enshrined in the language policy in Nigeria. The paper compares the policy statements on language in NPE 2004 and NPE 2014, highlighting major changes in the provisions on the language of instruction and curriculum implementation. It discusses the challenges posed by the language policy, its educational implications, and provides recommendations, such as the need for the policy to establish a more adaptable framework that allows for regional modifications based on the linguistic needs of pupils. This would enable local educational authorities to tailor language instruction to their specific contexts. Additionally, the government should provide targeted teacher training and resources to equip language teachers with the necessary skills and tools to effectively teach in indigenous languages. This could involve language-specific professional development programs and the creation of indigenous language teaching materials.